Testing the Advantages of Conscious vs. Unconscious Thought for Complex Decisions in a Distraction Free Paradigm - Todd McElroy; David L. Dickinson (Institute for the Study of Labor (IZA), 2016)
In this study we test predictions from Unconscious Thought Theory (UTT) that unconscious thought will lead to better decision making in complex decision tasks relative to conscious thought. Different from prior work testing this prediction, we use a method of manipulating conscious and unconscious thinking that is free from distraction. Specifically, we use a 3-week protocol to experimentally induce adverse sleep and circadian states, both of which should reduce deliberative, conscious thinking and therefore increase the relative importance of more automatic unconscious processes. Our findings fail to support UTT predictions and instead coalesce with other replication attempts that cast doubt on the superiority of unconscious processing in complex decision making.
Keywords: C91; D03; 330; sleep restriction; circadian; complex decisions; decision making; unconscious reasoning; sleep; experiments; behavioral economics